The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/hsr2.427
|View full text |Cite
|
Sign up to set email alerts
|

Mortality risk factors in kidney‐transplanted patients with COVID‐19: A systematic review and regression analysis

Abstract: Background and aims The kidney transplant patients who receive immunosuppressive and specific medication may lead to different mortality risk factors between kidney transplant patients with COVID‐19 and the general population. We aimed to provide a model predictor and a risk analysis of mortality in kidney transplant COVID‐19 positive patients. Methods We performed our search using PubMed, MEDLINE, Web of Science, Scopus, and Google Scholar to identify English articles published from the beginning of December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
(127 reference statements)
0
1
0
1
Order By: Relevance
“…En la caracterización de nuestra población con trasplante renal, se encontró que las comorbilidades más frecuentes fueron hipertensión arterial, enfermedad tiroidea y diabetes mellitus. En la literatura mundial se han descrito la hipertensión arterial y la diabetes mellitus como factores de riesgo para mortalidad y severidad en COVID-19 en receptores de trasplante renal (18)(19)(20)(21)(22)(23). Encontramos también que la presentación clínica de la COVID-19 en pacientes trasplantados, es similar a la reportada en la población general, en la que predominan la fiebre y los síntomas respiratorios.…”
Section: Discussionunclassified
“…En la caracterización de nuestra población con trasplante renal, se encontró que las comorbilidades más frecuentes fueron hipertensión arterial, enfermedad tiroidea y diabetes mellitus. En la literatura mundial se han descrito la hipertensión arterial y la diabetes mellitus como factores de riesgo para mortalidad y severidad en COVID-19 en receptores de trasplante renal (18)(19)(20)(21)(22)(23). Encontramos también que la presentación clínica de la COVID-19 en pacientes trasplantados, es similar a la reportada en la población general, en la que predominan la fiebre y los síntomas respiratorios.…”
Section: Discussionunclassified
“…Several studies have reported that kidney transplant recipients with COVID-19 have a high mortality rate as high as 40% [ 1 6 ]. It has been shown that increasing age and the presence of comorbid diseases are associated with an increased risk of mortality [ 21 , 22 ]. In our study, all kidney transplant recipients recovered except one.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) proclaimed the Coronavirus disease 2019 (COVID-19) as a global pandemic in March 2020 [ 1 ]. The rapid emergence and subsequent dominance of new variants on a global scale have become characteristic features of SARS-CoV-2 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%